Cultural Da'wah of Sunan Kalijaga: Wayang as a Medium of Acculturation Between Local Culture and Global Islamic Values - Kamilah, Isfina Muzayyana; Syahadatina, Fina; Artagulin, Kesyia Habibah (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Acculturation in the development of cultural and Islamic values often encounters tensions that may lead to conflict. This study explores the cultural da'wah method of Sunan Kalijaga through wayang (traditional shadow puppetry) as a medium for bridging Javanese local culture and Islamic values. It further examines the integration of John Fiske’s cultural theory with the symbolic meanings embedded in wayang performances, and assesses the influence of wayang as a tool of acculturation in shaping the cultural identity of the Javanese people.Using a descriptive-qualitative method based on library research, the study draws on primary sources related to wayang, as well as secondary sources such as scholarly articles and literature on Sunan Kalijaga’s cultural strategies and Islamic-themed cultural expressions. The analysis employs John Fiske’s three-tiered cultural framework—reality, representation, and ideology—to interpret the signs and meanings within the wayang medium in relation to Islamic values.The findings reveal that Sunan Kalijaga’s use of wayang as a cultural da'wah instrument enabled the harmonious integration of Islamic teachings with Javanese traditions. This strategy proved effective and widely accepted, particularly among Muslim communities in Java, thereby contributing to the formation of a unique cultural-religious identity in the region.